2020
DOI: 10.1016/j.cegh.2020.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Scrub typhus: A serious public health issue in Nepal

Abstract: The agro-climatic conditions, socio-economic situation, poor sanitation, low hygiene and health standards in Nepal are major contributing factors to the emergence of scrub typhus in Nepal. These outbreaks, along with poor diagnostic facilities, can lead to severe economic losses in a resource-limited country like Nepal. Diseases like avian influenza, leptospirosis, brucellosis, tuberculosis and rabies, that cause heavy socio-economic burden, have received huge attention of Government of Nepal and hence are amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Scrub typhus is emerging as a major public health problem in Nepal with reports of its occurrence from several widely reported geographic areas [ 12 , 13 ]. Despite reports of serological evidence of scrub typhus [ 10 ], Nepalese molecular surveys have been largely limited to studies of chiggers mite samples and samples from rodents [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scrub typhus is emerging as a major public health problem in Nepal with reports of its occurrence from several widely reported geographic areas [ 12 , 13 ]. Despite reports of serological evidence of scrub typhus [ 10 ], Nepalese molecular surveys have been largely limited to studies of chiggers mite samples and samples from rodents [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among India, Bangladesh, Nepal and Bhutan, only Bhutan has declared ST as a notifiable disease so far. Community and hospital based serosurveillance reports are available from these four countries providing evidence of endemicity of ST 8 10 42 43 44 . Similar reports are also available for Assam and Bihar 45 46 .…”
Section: Observationsmentioning
confidence: 99%
“…Similar hospital based sero-surveillance studies for scrub typhus showed seropositivity against O. tsutsugamushi viz . Bangladesh (16.6%), Nepal (52.6%), Bhutan (22.6%), and in the Indian States of Assam (20.3%), Bihar (25%) and West Bengal (10.5%) (at NBMCH) among AFIs 8 10 44 45 46 49 .…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 The epidemiological data related to Scrub typhus is minimum as it is not considered a priority disease in Nepal compared to avian influenza, rabies, and other zoonotic diseases. 15 Nevertheless, EDCD (Epidemiology and Disease Control Division) of Nepal has developed the guidelines for prevention and control of scrub typhus but these guidelines have rarely been implemented. 16 In 2021, various districts in Nepal saw rise in Scrub Typhus cases with 28 reported cases in Bajura District and 22 cases in Baitadi until mid of September.…”
Section: Introductionmentioning
confidence: 99%